17-β-Estradiol and Progesterone as Efficient Predictors of Survival in Older Women Undergoing Hip Fracture Surgery - Zhang, Yinwang; Xu, Zhen; Zhang, Jingyuan; Tang, Jie; Liu, Fuhai; Song, Yunxiao; Chen, Jie (Frontiers in Medicine, 2020)
Objective: Sex hormones have been linked to fractures in older women. The purpose of this present study was to investigate the prognostic impact of preoperative sex hormone levels on 30-day mortality in older women undergoing hip fracture surgery. Methods: A total of 157 female subjects with hip fractures were eligible for the study conducted from January 2010 to December 2019. The serum levels of sex hormones (follicle-stimulating hormone, prolactin, progesterone, testosterone, luteinising hormone and 17-β-estradiol [E2]) were measured at admission. To evaluate the prognostic significance of sex hormone levels, Cox proportional hazard models and Kaplan–Meier analyses were applied. Results: Of the 157 subjects, 13 (8.28%) deceased within 30 days. The deceased subjects had lower progesterone (P = 0.021) and E2 (P < 0.001) levels than the surviving group. Higher progesterone (HR = 0.168, 95%CI = 0.037–0.673) and E2 (HR = 0.857, 95%CI = 0.690–0.968) levels were the key protective factors for 30-day mortality in older women undergoing hip fracture surgery. Survival analysis showed that subjects with lower E2 or/and progesterone levels had a significantly higher percentage of 30-day mortality (log-rank test, P < 0.05). Conclusion: E2 and progesterone might be effective predictors of 30-day mortality in older women undergoing hip fracture surgery.